THE EARLIEST INSECT ENDOPHYTIC OVIPOSITION (EARLY PENNSYLVANIAN, EASTERN UKRAINE) - Dernov, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The world's oldest insect endophytic oviposition from the deposits of the Mospinka Formation (Upper Bashkirian, Lower Pennsylvanian) of the Donets Basin is described in the paper. There is little information on Carboniferous endophytic oviposition of insects. The earliest insect endophytic oviposition specimens are specimens from the Upper Moscovian and the uppermost part of the Gzhelian of Germany, as well as the uppermost Gzhelian of France and the USA. The endophytic oviposition described in this article is almost 10 million years older than specimens from the Upper Moscovian of Germany. The studied material was collected on five localities and four stratigraphic levels. The study area is the upper reaches of the Velyka Kamyanka River (southern part of the Luhansk Region, Ukraine). The rocks with the studied oviposition were formed in shallow marine, lagoonal and lacustrine environments. Insect damages were noted on leaves of arborescent lycopsids and cordaitaleans, and pteridosperm rachises. The above mentioned oviposition belongs to the following damage types sensu Labandeira et al., 2007: DT76, DT100, DT101 and DT175. The studied oviposition occurs mainly in sediments formed in the environments of a highly watered coastal alluvialdeltaic lowland with associations of the semi-aquatic sphenopsids (shores of lakes, rivers, and freshened lagoons), predominantly arborescent lycopsids (swampy areas), as well as pteridosperms on the elevated areas of accumulation plain. The most likely producers of endophytic oviposition are representatives of Odonatoptera, Palaeodictyopteroidea, and Orthoptera. The new findings substantially supplement the fossil record of insect endophytic oviposition.
Keywords: Ukraine; Donets Basin; Bashkirian Stage; endophytic oviposition; insects